Outcomes of non–acute coronary syndrome patients discharged from the emergency department with troponin positivity. Issue 1 (January 2014) - Brunner, Nathan W.; Scheuermeyer, Frank X.; Grafstein, Eric; Ramanathan, Krishnan
ABSTRACT: Background: Cardiac troponin elevation portends a worse prognosis in diverse patient populations. The significance of troponin elevation in patients discharged from emergency departments (EDs)without inpatient admission is notwell known. Methods: Patients without a diagnosis of acute coronary syndrome discharged fromtwo EDs between April 1, 2006, and December 31, 2007, with an abnormal cardiac troponin (troponin positive [TP]) were compared to a troponin-negative (TN) cohort matched for age, sex, and primary discharge diagnosis. Outcomes were obtained by linking with a regional ED and a provincial vital statistics database and adjusted for the following: estimated glomerular filtration rate, do-not-resuscitate status, history of coronary artery disease, Canadian Triage and Acuity Scale, and left ventricular hypertrophy on electrocardiography. The primary outcome was a composite of death or admission to hospital within 1 year. Results: Our total cohort (n 5 344) consisted of 172 TP and 172 TN patients. In the univariate analysis, TP patients had a higher rate of the primary outcome (OR 3.2, 95% CI 2.1–5.0, p < 0.001) and both of its components (p < 0.001). After adjusting for covariates, positive troponin remained an independent predictor of the primary outcome (OR 2.1, 95% CI 1.3–3.4, p 5 0.005) and inpatient admission (OR 2.0, 95% CI 1.2–3.4, p 5 0.006). There was no significant difference in death (OR 1.3, 95% CI 0.6–2.9, p 5 0.5) after adjustment. Conclusions: A positive troponin assay during ED stay in discharged patients is an independent marker for risk of subsequent admission. Our findings suggest that the prognostic power of an abnormal troponin extends to patients discharged from the ED.